Optoelectronic Properties of a Cylindrical Core/Shell Nanowire: Effect of Quantum Confinement and Magnetic Field - Mohamed El-Yadri; Jawad El Hamdaoui; Noreddine Aghoutane; Laura M. Pérez; Sotirios Baskoutas; David Laroze; Pablo Díaz; El Mustapha Feddi (Nanomaterials, 2023)
This study investigates the effect of quantum size and an external magnetic field on the optoelectronic properties of a cylindrical Al<semantics>x</semantics>Ga<semantics>1−x</semantics>As/GaAs-based core/shell nanowire. We used the one-band effective mass model to describe the Hamiltonian of an interacting electron-donor impurity system and employed two numerical methods to calculate the ground state energies: the variational and finite element methods. With the finite confinement barrier at the interface between the core and the shell, the cylindrical symmetry of the system revealed proper transcendental equations, leading to the concept of the threshold core radius. Our results show that the optoelectronic properties of the structure strongly depend on core/shell sizes and the strength of the external magnetic field. We found that the maximum probability of finding the electron occurs in either the core or the shell region, depending on the value of the threshold core radius. This threshold radius separates two regions where physical behaviors undergo changes and the applied magnetic field acts as an additional confinement.